Patient-specificity of scapular orientation measurements using an acromion marker cluster with multiple calibration poses. (17th July 2020) - Zaferiou, Antonia M.; Knowlton, Christopher B.; Jang, Suk-Hwan; Saltzman, Bryan; Verma, Nikhil; Forsythe, Brian; Nicholson, Gregory; Romeo, Anthony A.
Abstract: The purpose of this study was to understand how each calibration pose affects scapular orientations measured by an Acromion Marker Cluster during scapular plane arm elevation performed by patients who had been pre-operatively indicated for Reverse Total Shoulder Arthroplasty. Eight pre-operative Reverse Total Shoulder Arthroplasty patients participated in this study while optical motion capture measured kinematics, specifically scapulothoracic angles and angular displacements, vs. humerothoracic elevation. The angle measurements were compared across the static calibration poses used to calculate them within-patient with One Dimensional Statistical Parametric Mapping paired t-tests and across-patients with a series of Sign Tests. The study uncovered patient-specificity in the effects of the Acromion Marker Cluster calibration pose on scapulothoracic angles and near linear offsets between the scapulothoracic upward rotation angles. The scapulothoracic upward rotation angular displacement measurements across calibration poses were within 5° of each other, suggesting nearly linear offsets between upward rotation angle measurements from each calibration pose. The Sign Tests revealed that using the Neutral calibration pose estimated significantly greater scapulothoracic protraction angles during arm elevation than did using the Hand to Back Pocket calibration pose (p = 0.02). Scapulothoracic protraction and posterior tilt measurements were near linear offsets between calibration poses only when humerothoracic elevation was less than 50°. Results encourage patient-specific and humerothoracic elevation-specific methods to combine calibration poses and the development of standards to report scapulothoracic orientations derived from using an Acromion Marker Cluster with multiple calibration poses.